(untitled) (Tokyo, Japan,Singapore, 1997)
Contents: Part 1 Industrial policies in industrialized northeast asian economies, Part 2 Industrial policies in the entrepôt nies, Part 3 Industrial policies in southeast asian developing economies
Keywords: Industrial policy,Chính sách công nghiệp; East Asia,Đông Á